An analysis of chip breaker tool effect on an oblique cutting process using a coupled thermo-elasticplastic FEM. (1st January 2001) - Lin, Zone-Ching; Lin, Yeou-Yih
The finite deformation theory, an updated Lagrangian formulation (ULF), a 3D finite difference equation for heat transfer, and a two-stage geometrical equation for an obstruction-type chip breaker tool face were used to describe the oblique cutting process. Thus, a coupled thermo-elastic-plastic large deformation finite element model for oblique cutting with an obstruction-type chip breaker tool was established. Mild steel was used for the workpiece, tool as P20 and the cutting speed was 274.8 mm/s. The chip deformation process, the variations of the cutting force, specific cutting energy, both stress and temperature distributions on the chip surface and residual stresses on the machined workpiece surface were analysed for different chip breaker lengths. The findings indicate that the shorter the chip breaker length, the lower the values of the aforementioned physical properties and the better the effect of chip breaking.